PERANAN SEKERTARIS DAERAH DALAM MENINGKATKAN PELAKSANAAN TUGAS POKOK DAN FUNGSI PERANGKAT SEKRETARIAT DAERAH KABUPATEN SIDENRENG RAPPANG - Rahmatiah Rahmatiah (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
This study aims to determine the role of the regional secretary in improving the implementation of the main tasks and functions of the regional secretariat of Sidenreng Rappang Regency, namely the success, management, appointment of employees, transfer of employees and dismissal of employees and to determine the factors that influence the role of the regional secretary in improving the implementation of the main tasks and the functions of the Regional Secretariat of Sidenreng Rappang Regency, namely personality, expectations, characteristics, needs, and policies taken. The research was conducted from December 2014 to January 2015 at the Sidenreng Rappang Regency Regional Office using a population of 132 people using 33 samples. Determination of the sample used is to take 25% of the existing population, from the results of data collection with random sampling technique. The analysis used is through a descriptive approach, namely answering and solving problems by understanding and deepening thoroughly and completely from the object under study in order to obtain a clear picture. The results showed that the role of regional secretaries on the main tasks and functions of regional apparatuses can be said to be good, this can be seen from the performance dimension, namely the performance of regional apparatus which has 2.82 and the performance of regional secretaries which has 3.27 and if accumulated, the results are good. Meanwhile, the factors that affect the performance of the regional secretary are the personality of the regional secretary with a score of 3.15, the expectations of the regional secretary on the performance of his staff with a score of 2.55, the need for the regional secretary with a score of 2.91, policies issued by the regional secretary with a score of 3, 24, while what needs to be addressed is the characteristics of the regional secretary who has a score of 2.42.